Storage Ability and Sensory Quality of ‘Reinette Simirenko’ Apples Treated with Ethephon and 1-MCP - Drozd Olha; Melnyk Oleksandr; Remeniuk Leonid (Journal of Horticultural Research, 2025)
In order to develop a more effective method for the storage and preservation of excellent taste of late-winter apple ‘Reinette Simirenko’, the effects of preharvest treatment of trees with ethylene-producing ethephon, a three-day delay in postharvest cooling of the fruit and their treatment with the ethylene inhibitor 1-methylcyclopropene (1-MCP) were studied. The experimental design included the following treatments: 1 – no ethephon treatment, no cooling delay, no 1-MCP treatment (control); 2 – no ethephon treatment, no cooling delay, with 1-MCP treatment; 3 – no ethephon treatment, with cooling delay, no 1-MCP treatment; 4 – no ethephon treatment, with cooling delay and 1-MCP treatment; 5 – ethephon treatment, no cooling delay, no 1-MCP treatment; 6 – ethephon treatment, no cooling delay, with 1-MCP treatment; 7 – ethephon treatment with cooling delay, no 1-MCP treatment; 8 – ethephon treatment, with cooling delay, and 1-MCP treatment. During harvest and storage, ethylene emission, apple flesh firmness, dry soluble solids content, titratable acidity, iodine–starch test (CTIFL scale), and the Streif index were determined (the last two indicators were determined only during fruit collection). Apples were stored at a temperature of 2 ± 1 °C and air humidity of 90–93%. Our research revealed that preharvest treatment of trees with ethephon and a three-day delay in cooling of freshly picked apples accelerated fruit ripening during storage – greater natural losses, higher ethylene activity, and a faster decline in flesh firmness and titratable acid content were observed. During six months of storage, regardless of the treatment of trees with ethephon and delayed fruit cooling, postharvest treatment of apples with 1-MCP prevented the development of fungal diseases and functional disorders, reduced natural losses and ethylene activity, and ensured high flesh firmness, a higher content of dry soluble solids and titratable acids. Preharvest treatment of trees with ethephon improved the taste of ‘Reinette Simirenko’ apples treated with 1-MCP, regardless of the delay in postharvest cooling.